BATARI HIYANG JANAPATI DALAM PERSPEKTIF GENDER - Elis Suryani NS (Badan Pengembangan dan Pembinaan Bahasa, 2017)
The life of Indonesian society is dominant with patriarchal culture that puts women always under the shadow of men. In, the perception of social structure of society, women are always underestimated. In Indonesia, many women are also oppressed and abused. Women in a patriarchal culture are always considered helpless and should always be dependent on men, in the Sundanese language proverb, there is an